Efektivitas Penerbitan KIA (Kartu Identitas Anak) Melalui Aplikasi Dukcapil Smart Kabupaten Bantul Tahun 2019 - Sitti Ajeng Nurqarimah Taliu; Suranto Suranto (Universitas Teuku Umar, 2020)
Disdukcapil (Population and Civil Registration Service) of Bantul Regency based on Permendagri No.2 of 2016 concerning Child Identity Card to meet the identified needs of children, where KIA, in this case, is intended to be the same as KTP-EL, namely as a sign of population, the difference is KTP-EL is intended to be owned by people aged 17 years and over, while KIA is for children under 17 years of age. Through technological advances like today, the millennial era is of course very updated regarding various attractive offers such as discounts or information that are beneficial to millennials, for this reason, the Bantul Regency Disdukcapil seeks to maximize their performance to continue to support the number of KIA making, especially in Bantul Regency. The method used in this research is descriptive qualitative research. Based on the results found by researchers through the concept of effectiveness using 3 variables, namely Goal Achievement, Integration, and Adaptation. From the results of this study, the researchers concluded that the effectiveness of MCH issuance through the Dukcapil Smart application in Bantul Regency in 2019 is quite effective in making MCH through the Dukcapil Smart application but has not been effective in adapting MCH applications through the Dukcapil Smart application.